2013
DOI: 10.3389/fphys.2013.00266
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in skeletal muscle and their regulation with exercise, ageing, and disease

Abstract: Skeletal muscle makes up approximately 40% of the total body mass, providing structural support and enabling the body to maintain posture, to control motor movements and to store energy. It therefore plays a vital role in whole body metabolism. Skeletal muscle displays remarkable plasticity and is able to alter its size, structure and function in response to various stimuli; an essential quality for healthy living across the lifespan. Exercise is an important stimulator of extracellular and intracellular stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
82
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 132 publications
(174 reference statements)
3
82
0
1
Order By: Relevance
“…miR-1, miR133a/b, and miR-206), with miR-1 being the most highly expressed miRNA (73,677) followed by miR-206 (29,603). NonmyomiRs such as miR-709 (28,395) and miR-26a (20,464) were also expressed at high signal intensities (Table 6). Of the 700 miRNA probes examined in the stretched and unstretched diaphragms from mdm mice (Fig.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…miR-1, miR133a/b, and miR-206), with miR-1 being the most highly expressed miRNA (73,677) followed by miR-206 (29,603). NonmyomiRs such as miR-709 (28,395) and miR-26a (20,464) were also expressed at high signal intensities (Table 6). Of the 700 miRNA probes examined in the stretched and unstretched diaphragms from mdm mice (Fig.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…For example, skeletal muscles from elderly people display an elevated levels of let-7b and -7e when compared with that from younger people, and the most highly ranked cellular processes likely to be regulated by let-7b and let-7e miRNAs are associated with cell cycle regulation and cellular growth and proliferation (71). Another study has shown that the primary role of let-7 members is the possession of a conserved function as a tumor suppressor, and therefore they are able to down-regulate the expression of genes associated with cell proliferation, thereby promoting differentiation of human and mouse neuronal stem cells (20). A recent study has identified PABP2 (poly(A)-binding protein) as a genetic interaction partner of the let-7 miRNA (72); the phenotypes associated with human PABP2 mutation in oculopharyngeal MD (a late-onset, progressive disease) seem to affect selectively only muscle cells (73).…”
Section: Volume 290 • Number 41 • October 9 2015mentioning
confidence: 99%
“…The primary function of miRNAs is to decrease protein levels either by repressing gene translation or promoting the degradation of target mRNAs, of which the latter accounts for the majority of miRNA activity (43). Given their purported role in posttranscriptional regulation, miRNAs have emerged as a potential regulator of exercise-induced adaptations in skeletal muscle (90). The expression of various miRNA species in human skeletal muscle is altered following both single bouts of exercise (31,72,91) and after short-term exercise training (26,72).…”
mentioning
confidence: 99%
“…Additional molecular mechanisms with the potential to regulate skeletal muscle adaptations to exercise have recently emerged, including altered microRNA (miRNA) expression (90). miRNAs are small (ϳ20 -30 nucleotides in length), noncoding ribonucleic acid (RNA) species that are highly expressed in skeletal muscle (90).…”
mentioning
confidence: 99%
See 1 more Smart Citation